Pandemi Covid-19 dalam Telaah Kritis Sosiologi Pendidikan - Ahmad Shofiyuddin Ichsan (Universitas Musamus, Merauke, Papua, 2020)
Abstract: This study aims to find out how social change, especially in education, is caused by the Covid-19 pandemic in the perspective of educational sociology, namely through the functionalism theory and the constructivism theory. This type of study is a library research with data collection taken from articles, journals, documents, mass media, internet, statistical data, and other related literature sources. The results obtained that the functionalism theory tries to understand how the educational elements with each other elements have their respective functions which are interrelated and become a whole system, namely social, action, cultural, and personality systems. Whereas the constructivism theory tries to outline two big ideas, that students construct their own knowledge and the existence of social interaction as the constructional aspects of their knowledge. Related to education in the Covid-19 pandemic era, there are three forms of constructivism described, namely individual, social, and dialectical constructivism. Keywords: Covid-19 pandemic; sociology of education; social transformation